Filosofi Dakwah KH. Muhammad Khoiron Syu’aib di Lokalisasi Surabaya - Sunarto AS (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2016)
Kiai Khoiron is a unique figure who has conduct-ed an intensive dakwah (religious propaganda) at the localiza-tion of Surabaya. Through his exceptional method of dakwah, there have been many prostitutes and the pimps who have repented. Preaching in an unusual environment has certainly resulted in a particular phenomenon. This article intention-ally presents Kiai Khoiron’s method of dakwah. Employing descriptive-qualitative approach, the article explores the phenomenon of dakwah promulgated by Kiai Khoiron. It deals with approaches, characteristics, and typology of dakwah conducted by Kiai Khoiron to the residents of localization, prostitutes, and pimps. The findings of this study suggest that the approach of dakwah is centered upon the objects (mad‘û), i.e. the people of the localization. He seeks to change religious views held by the objects (mad‘û), not only at the level of understanding, but also their attitudes and behaviors. All the elements of propaganda delivered certainly conform to the conditions of the objects, either in the form of by-speech propaganda (bi al-lisân) or by-example preaching (bi al-hâl). With reference to the materials and approaches of dakwah carried by Kiai Khoiron, it seems that he can be characterized as an adaptive, attentive, solution-giver, and humorous preacher.